Probabilistic analysis of the wear process during the operation of the coatings under friction conditions - Щепетов, В. В.; Громенко, В. Ю.; Амасович, Ю. І.; Лісовий, Є. М. (Proceedings of National Aviation University (archive), 2002)
Considered from the standpoint of the structural-energy friction concept, the probabilistic analysis of the process wear and tear in the conditions of operational damage